2002
DOI: 10.1524/ract.2002.90.9-11_2002.575
|View full text |Cite
|
Sign up to set email alerts
|

XAS study of technetium(IV) polymer formation in mixed sulphate/chloride media

Abstract: SummaryX-ray absorption spectroscopy has been used to establish polymer formation of Tc(IV) in aqueous solutions of NaAs the molybdenum chemistry show similarities to that of technetium, we used MoOIn aqueous solution, some polymers are formed regardless to the nature of the media composition: Tc-Tc=2.50 ± 0.02 Å. The general structure is in agreement with a first coordination shell containing 6 O. The modelling shows that, in the first coordination shell, there is no chloride ligand. The observed geometries a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 15 publications
8
33
0
Order By: Relevance
“…This hypothesis was based on the belief that Tc(IV) and Fe(III) would precipitate in intimate association after either homogeneous or heterogeneous reaction. Given the known tendency of Tc(IV) to favor a hexacoordinate motif in aqueous complexes (Ben Said et al, 2000;Vichot et al, 2002) and crystalline solids (Rogers et al, 1969;Vichot et al, 2002), we further speculated that sorbed Tc(IV) would exist in an octahedral environment distributed within the Fe(III) oxide structure. In contrast, the best fit model to the Tc-EXAFS data was found to be a single Tc(IV) 2 O 10 octahedral dimer linked in edge-sharing mode to a single Fe(III)-O octahedral site in ferrihydrite.…”
Section: Tc In the Redox Reaction Productmentioning
confidence: 91%
See 2 more Smart Citations
“…This hypothesis was based on the belief that Tc(IV) and Fe(III) would precipitate in intimate association after either homogeneous or heterogeneous reaction. Given the known tendency of Tc(IV) to favor a hexacoordinate motif in aqueous complexes (Ben Said et al, 2000;Vichot et al, 2002) and crystalline solids (Rogers et al, 1969;Vichot et al, 2002), we further speculated that sorbed Tc(IV) would exist in an octahedral environment distributed within the Fe(III) oxide structure. In contrast, the best fit model to the Tc-EXAFS data was found to be a single Tc(IV) 2 O 10 octahedral dimer linked in edge-sharing mode to a single Fe(III)-O octahedral site in ferrihydrite.…”
Section: Tc In the Redox Reaction Productmentioning
confidence: 91%
“…The Tc-Fe disorder was unreasonably large and the fit to the second transform peak was not ideal, especially in terms of phase. The model was consequently extended to allow for the formation of TcO 2 polymers (Vichot et al, 2002). These polymers could then coordinate to the ferrihydrite surface or vacancy sites.…”
Section: Xanes and Exafs Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments with high concentrations of technetium (greater than10 -5 M Tc), several investigators have reported formation of colloids of technetium at moderately acidic (pH ≤4) Sekine et al 2004;Vichot et al 2002) and under reducing conditions (Sekine et al 2002). They report brown to brownish-black turgid solutions that are consistent with the presence of colloids.…”
Section: Colloidsmentioning
confidence: 99%
“…The proposed mechanism of TcO 2 ÁnH 2 O formation involves Tc(IV) polymerization into soluble TC n O ð4nÀ2yÞþ y chains that consequently precipitate into TcO 2 ÁnH 2 O after a critical cluster size is attained (Vichot et al, 2002;Maes et al, 2004). The formation of TcO 2 polymeric chains prior to precipitation might explain the formation of similar post-reaction products in different systems, and the observance of clusters (n < 5) in some systems and precipitates (n > 10) in others.…”
Section: Tc(iv) Reaction Productmentioning
confidence: 99%